INTERNATIONAL CLASSIFICATION OF FUNCTIONING, DISABILITY AND HEALTH FOR STROKE - Liliana Cristina Amaro Relhas; Ricardo Filipe Pereira Ramos; Ana Cristina Lopes Figueiredo; Ana Isabel Gouveia Da Silva Braga; Helena Castelão Figueira Carlos Pestana; Luis Manuel Mota Sousa (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Background: Stroke is a cardiovascular disease with the highest prevalence worldwide, with impact on the functionality of survivors. Objective: To identify the Score Set of the International Classification of Functioning, Disability and Health (ICF) for people after stroke. Material and Methods: The research question was performed according to the Joanna Briges Institute (JBI) recommendations and PICo framework (Population, Interest phenomenon, Context). Each dimension of the PICo contributed to the definition of inclusion criteria, namely Population (P) Person after stroke; Interest phenomenon (I) Score set ICF; Context (Co) Community. The electronic research was done in the Medline, SciELO, virtual health library and EBSCO databases, between 2013 and 2017 Results: Of the identified articles 11 were selected and 160 ICF codes were identified, which characterize the functionality of people after stroke. Of these 160 codes, it was verified that 21, divided by 3 ICF categories, presented a frequency greater than or equal to 50%. Conclusions: The ICF score set for people after stroke is distributed as follows: 6 Body Functions (29%), 13 Activity and Participation (61%) and 2 Environmental Factors (10%).